Hubungan Keterampilan Berpikir Kritis dengan Hasil Belajar Siswa Sekolah Dasar - M. Misbachul Huda; Lazuardi Rahman (Jurnal Pena Karakter : Jurnal Pendidikan Anak dan Karakter, 2020)
The aim of this study was to reveal the relationship between critical thinking skills and student learning outcomes. Critical thinking skills have already been important research material in 21st-century learning activities. Students with critical thinking skills always evaluate ideas systematically and logically. Ideas were evaluated through a cognitive activity that was analytical thinking and uses mental processes in decision making. In addition, learning activities were inseparable from student learning outcomes because those were indicators to evaluate learning activities. This raises questions about the relationship between critical thinking skills and student learning outcomes, especially in elementary schools. This research used correlational design. Critical thinking skills and students learning outcomes were measured by written test. Data were analyzed with ANOVA and regression analysis. The subject of the research was the fifth-grade elementary school students. The results showed that there was a significant relationship between critical thinking skills and student learning outcomes. As an implication, these discoveries of research are needed by teachers in developing critical thinking skills in elementary school.